2013
DOI: 10.1007/s00134-013-2863-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trials of 6 % tetrastarch (hydroxyethyl starch 130/0.4 or 0.42) for severe sepsis reporting mortality: systematic review and meta-analysis

Abstract: PurposeTo assess the impact of 6% tetrastarch (hydroxyethyl starch (HES) 130/0.4 and 130/0.42) in severe sepsis patients. The primary outcome measure was 90-day mortality. MethodsA structured literature search to identify prospective randomized controlled trials (RCT) in adult patients with severe sepsis receiving 6% tetrastarch (potato or waxy maize origin), as part of fluid resuscitation in comparison to other non-HES fluids after randomisation, in the critical care setting was undertaken. A systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 64 publications
(109 reference statements)
1
44
1
2
Order By: Relevance
“…(Grade 2+) STRONG agreement Rationale: Several randomized or observational studies and meta-analyses have examined the beneficial effect of a preferential administration of colloids compared to crystalloids [62][63][64][65][66][67][68][69][70][71][72][73]. In the ICU, the use of HES, regardless of its type, has been reported to be associated with an increase in mortality rate, AKI incidence and the need for RRT in several meta-analyses with a high level of proof [58][59][60][61][62][63][64][65][66][67][68][69][70][71]73]. A Cochrane meta-analysis simultaneously considering all colloids did not find any beneficial effect associated with the preferential use of colloids, regardless of nature, compared with crystalloids.…”
Section: How To Assess the Risk Of Akimentioning
confidence: 99%
“…(Grade 2+) STRONG agreement Rationale: Several randomized or observational studies and meta-analyses have examined the beneficial effect of a preferential administration of colloids compared to crystalloids [62][63][64][65][66][67][68][69][70][71][72][73]. In the ICU, the use of HES, regardless of its type, has been reported to be associated with an increase in mortality rate, AKI incidence and the need for RRT in several meta-analyses with a high level of proof [58][59][60][61][62][63][64][65][66][67][68][69][70][71]73]. A Cochrane meta-analysis simultaneously considering all colloids did not find any beneficial effect associated with the preferential use of colloids, regardless of nature, compared with crystalloids.…”
Section: How To Assess the Risk Of Akimentioning
confidence: 99%
“…In addition, more recent meta-analysis showed an increased amount of acute kidney injury and a trend towards a higher mortality in patients with severe sepsis and septic shock treated with HES solutions compared to crystalloid solutions. [50][51][52][53] These findings led to an investigation of the European authorities concerning the risk of HES products and, as a first consequence, to a withdrawal of all starch products from the UK market. The Food and Drug Administration (FDA) recommended that HES should not be used in critically ill patients or in patients with pre-existing renal disease.…”
Section: Clinical Datamentioning
confidence: 99%
“…Dear Editor, We read with interest the recent systematic review investigating the impact of hydroxyethyl starch administration as part of initial fluid resuscitation for severe sepsis on mortality [1]. The authors claimed to have identified ''prospective randomised controlled trials (RCTs) in adult patients with severe sepsis receiving 6 % tetrastarch (of potato or waxy maize origin) as part of fluid resuscitation in comparison with other non-HES fluids after randomisation in the critical care setting''.…”
mentioning
confidence: 99%
“…The authors claimed to have identified ''prospective randomised controlled trials (RCTs) in adult patients with severe sepsis receiving 6 % tetrastarch (of potato or waxy maize origin) as part of fluid resuscitation in comparison with other non-HES fluids after randomisation in the critical care setting''. They put emphasis on ''initial fluid resuscitation'', since in the concluding remarks they state that ''90-day mortality were significantly higher in severe sepsis patients receiving 6 % tetrastarch 130 kDa solutions as part of initial fluid resuscitation'' [1]. Bearing that in mind, we wonder why the authors included reference 41 in which patients were randomized to either 6 % HES 130/0.4, 250 ml every 6 h, or 20 % albumin, 100 ml every 12 h [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation